Stable cellulose-based carbon molecular sieve membranes with very high selectivities - Tiago Araújo (2022)
Carbon molecular sieve membranes (CMSMs) with a remarkable separation performance and stability were prepared from an ionic liquid regenerated cellulose precursor. Extremely high selectivities to H2 and CO2 are reported (H2/CH4 > 206 000 and CO2/CH4 > 14 600) due to the precise pore size of the produced membranes. Selectivity results >3590 are reported for the first time for the C3H6/C3H8 separation using cellulose-based CMSMs. However, after one year exposed to ambient air the permeability of these CMSMs to O2 reduced approximately 62% and the O2/N2 selectivity increased 72% due to the chemisorption of oxygen. In this work it is demonstrated that exposure to propylene can not only regenerate the aged CMSMs but, more importantly, it can passivate them in a long-lasting way. CMSMs exposed to propylene for 10 days acquired aging-resistant properties that last for more than 1 year, i.e. they preserve their separation performances after 1 year exposed to ambient air. The regeneration of these CMSMs using propylene causes an increase in the permeability to O2 and in the O2/N2 selectivity of aged CMSMs. The effect of oxygen chemisorption and the passivation and regeneration by propylene post-treatment were evaluated by adsorption isotherms, FTIR, XPS and Raman spectra. Transport properties were evaluated for O2 and N2. The propylene post-treatment reduced the fraction of oxygenated groups on the surface of the CMSM, causing the widening of the pores, changing the adsorption kinetics of the gases. The results presented in this work demonstrate the industrial attractiveness of this type of membranes for the separation of gases with high performance and stability.